IgG4-related diseases: state of the art on clinical practice guidelines. (19th January 2019) - Iaccarino, Luca; Talarico, Rosaria; Scirè, Carlo Alberto; Amoura, Zahir; Burmester, Gerd; Doria, Andrea; Faiz, Karim; Frank, Charissa; Hachulla, Eric; Hie, Miguel; Launay, David; Montecucco, Carlomaurizio; et al.
Abstract : Immunoglobulin G4-related diseases (IgG4-RD) are a group of chronic relapsing–remitting inflammatory conditions, characterised by tissue infiltration with lymphocytes and IgG4-secreting plasma cells, fibrosis and a usually favourable response to steroids. In this narrative review, we summarise the results of a systematic literature research, which was performed as part of the European Reference Network ReCONNET, aimed at evaluating existing clinical practice guidelines (CPGs) and recommendations in IgG4-RD. From 167 publications initially obtained from a systematic literature search, only one was identified as a systematic multispecialist, evidence-based, consensus guidance statement on diagnosis and treatment of IgG4-RD, which may be recommended for use as CPG in IgG4-RD. With the recognition of a limited evidence based in this increasingly recognised disease, the group discussion has identified the following unmet needs: lack of shared classification criteria, absence of formal guidelines on diagnosis, no evidence-based therapeutic recommendations and lack of activity and damage indices. Areas of unmet needs include the difficulties in diagnosis, management and monitoring and the scarcity of expert centres.